Examining the Relationship between Good Corporate Governance and Company Size on Stock Prices in Manufacturing Companies Listed on the Indonesia Stock Exchange - Syafei M. Nur, Imran; Ibrahim, Muhdi B. Hi.; Sonjaya, Yaya; Ridhwansyah Pasalo, Muhammad; Taotubun, Najaradin (Golden Ratio of Finance Management, 2022)
This study aims to determine the impact of excellent corporate governance ownership structure on the firm size on stock prices in manufacturing companies listed on the Indonesia Stock Exchange, both simultaneously and partially. According to the findings, good corporate governance, as evaluated by the board of directors and the commissioners, negatively and substantially impacts stock prices. In contrast, the audit committee has a positive and significant impact on stock prices. The natural logarithm of total assets, which measures the size of a company, has a favorable effect on stock prices. The more the company's total investments in the 52 issuers, the higher the share price. Managerial ownership has a positive but not statistically significant effect on stock prices, whereas institutional ownership has a negative and statistically significant impact. The increase in institutional ownership will cause stock prices to fall.